Strategic Management of Air Transportation in Terms of Market Share of Companies in Turkey - Dursun, Erdal (Current Studies in Social Sciences VI, 2023)
Abstract The major aim of this book chapter is to investigate the strategic management of air transportation in terms of market share of companies in Turkey. In this context, after the general concepts are discussed in the introduction part, the studies on the subject are given theoretically in the literature summary. How aviation companies will increase their market share within the framework of theories including and Porter generic strategies, organization orientation, production, selling, and marketing concept in the third part of book chapter. In the conclusion part, solution suggestions for aviation companies to increase their market shares are discussed as well.